Maternal cigarette smoking before and during pregnancy and the risk of preterm birth: A dose–response analysis of 25 million mother–infant pairs - Liu, Buyun; Xu, Guifeng; Sun, Yangbo; Qiu, Xiu; Ryckman, Kelli K.; Yu, Yongfu; Snetselaar, Linda G.; Bao, Wei (PLoS medicine, 2020)
Most of the women who smoke before pregnancy continue smoking during pregnancy, and some start to quit smoking after being pregnant, although existing guidelines for pregnancy recommend that women who smoke should quit smoking before pregnancy. Findings about the timing and intensity of maternal smoking, especially low-intensity smoking (1-9 cigarettes per day), and preterm birth are still inconsistent and ambiguous. This study aimed to examine the association of the timing of smoking and doses of smoking before pregnancy and during the first or second trimester of pregnancy with preterm birth in a large-scale population-based retrospective cohort study. We used nationwide birth certificate data from singleton mother-infant pairs in the United States National Vital Statistics System, 2011-2018. All adult women with live singleton births, without preexisting hypertension or diabetes, and with complete data on smoking and gestational age at delivery were included. Participants reported their smoking status (yes or no) and daily number of cigarettes consumed before and during each trimester of pregnancy. The outcome of interest was preterm birth, defined as a birth before 37 weeks of gestation. Logistic regression models were used to estimate the odds ratio (OR) with 95% confidence intervals (CIs) of preterm birth associated with smoking status and the number of cigarettes consumed, adjusting for maternal age, race/ethnicity, parity, education levels, prepregnancy BMI, previous history of preterm birth, marital status, infant sex, and initiation of prenatal care. This study included 25,623,479 women, with a mean age of 29 years (range 20-50 years); 13,742,486 (53.6%) participants were of non-Hispanic white ancestry, 5,971,598 (23.3%) of Hispanic ancestry, and 3,417,456 (13.34%) of non-Hispanic black ancestry. The prevalence of preterm birth was 9.3% (n = 2,378,398). We found that maternal smoking during pregnancy, even at a very low level of intensity, was associated with an increased risk of preterm delivery. The adjusted ORs (95% CI) of preterm birth for mothers who smoked 1-2, 3-5, 6-9, 10-19, and ≥20 cigarettes per day during the first trimester compared with mothers who did not smoke were 1.31 (1.29-1.33), 1.31 (1.30-1.32), 1.33 (1.31-1.35), 1.44 (1.43-1.45), and 1.53 (1.52-1.55), respectively (all P values < 0.001), whereas for those who smoked during the second trimester, the corresponding ORs were 1.37 (1.35-1.39), 1.36 (1.35-1.38), 1.36 (1.34-1.38), 1.48 (1.47-1.49), and 1.59 (1.58-1.61), respectively (all P values < 0.001). Furthermore, smokers who quit before pregnancy, regardless of smoking intensity, had a comparable risk of preterm birth with nonsmokers, although this was not the case when cessation occurred in the first or second trimester of pregnancy. The major limitation of this study is the self-reported information about smoking, which may be subject to information bias. In addition, we cannot rule out the possibility of residual confounding caused by unmeasured factors in an observational research design. In this study, we observed that low-intensity cigarette consumption during either the first or second trimester of pregnancy, even as low as 1-2 cigarettes per day, was associated with an increased risk of preterm birth. These findings suggest that there is no safe level or safe trimester for maternal smoking during pregnancy. Women of reproductive age who smoke should be strongly encouraged and supported to quit smoking before pregnancy.